Analisis Sinkronisasi RPJMD Kabupaten Karawang Tahun 2021-2026 dengan Rencana Strategis Dinas Pariwisata dan Kebudayaan Kabupaten Karawang Tahun 2021-2026 - Aldo Altas (Post Graduate School of Government Science, 2023)
The Regional Medium Term Development Plan (abbreviated as RPJMD) is an elaboration of the regional head's vision, mission and program which contains goals, targets, strategies, policy direction, regional development and regional finance, as well as regional apparatus programs accompanied by an indicative funding framework for the period of time 5 (five) years prepared by the Regional Government. Regional development planning must be in line with national priorities and national strategic targets, so the preparation of regional development plans is coordinated, synergized and harmonized by regional officials. This research aims to analyze the synchronization between the Medium-Term Regional Development Plan for Karawang Regency for 2021-2026 and the Strategic Plan for the Karawang Regency Tourism and Culture Office for 2021-2026. This research uses literature review techniques to find references that are relevant to the research topic. Researchers analyze topics by collecting information from various sources such as books, journals, articles, trusted websites, and so on online to produce writing. The research results show that synchronization between the Karawang Regency RPJMD and the Tourism Office Strategic Plan with Karawang Regency Culture has occurred. This can be seen from the aspects of strategic issues, goals, targets, strategies and policy directions which are interrelated and coordinated.